Influence of Chinese entrepreneurial companies' internationalization on independent innovation: Input incentive effect and efficiency improvement effect - Xin Xu; Yun Xia; Chuntao Li (China Journal of Accounting Research, 2017)
Within the special environment of the ChiNext market, we study how an internationalization strategy affects the independent innovation of Chinese entrepreneurial companies from two dimensions: R&D input and patent output. An internationalization strategy has a significant incentive effect on R&D input and a significant efficiency improvement effect on patent output. Entrepreneurial companies with higher degrees of internationalization have higher R&D inputs and patent outputs. After endogeneity is controlled, these effects still exist. Internationalization strategy has more pronounced effects on independent innovation in strategic emerging industries. The results elucidate the internationalization strategy and independent innovation of Chinese entrepreneurial companies, and have valuable implications for Chinese regulators in making international development policies for strategic emerging industries and independent innovation.
Keywords: O32; F23; 650; Internationalization; R&D; Patent output; Strategic emerging industries